Fabrication of Rough Polymer Surfaces Exhibiting Anti-reflective Properties. Issue 1728 (27th February 2015) - Mattaparthi, Srinadh; Sharma, Chandra S.
ABSTRACT: We have demonstrated some facile ways to fabricate the large area polymer surfaces with varying roughness followed by studying their anti-reflective properties. One of the approaches is based on electrospun nanofibers deposited on a substrate in an uneven non-woven matrix. This electrospun fabric was used as a master template to fabricate the negative replica of the fibers by soft lithography generating the roughness in polydimethylsiloxane (PDMS) surfaces. The second approach is based on biomimicking of flower petals. Petals are used as a master template to transfer surface features with hierarchical roughness over PDMS surface using replica moulding. As fabricated polymer surfaces with varied roughness have then tested for their anti-reflective properties using UV-VIS spectroscopy over a wide range of wavelengths and angles of incidence of light. These measurements show near zero reflection of patterned PDMS surfaces as compared to planar PDMS. This omnidirectional broadband anti-reflection behaviour of polymer surfaces can be used in wide variety of engineering applications including in solar cells.